PCA-SBM Model Green Urbanization Performance Assessment in China - Chen, Rui; Lu, Haochun (Frontiers in Energy Research, 2021)
China’s urbanization over the past thirty years has been the fastest in history and has led to significant challenges in balancing urbanization and energy use. As a result, this study proposed a comprehensive green urbanization assessment index system considering energy use and environment protection together. To be specific, principal component analysis was applied to eliminate redundant information, and a slacks-based measure model was used to evaluate urbanization efficiencies. Meanwhile, with super efficiency incorporated, the proposed model enabled to distinguish the DMU from DMUs with same efficiency value, further, a projection analysis was conducted to direct the improvement of the identified inefficient decision-making units (DMUs). Finally, the comprehensive green urbanization index system was applied to a western Chinese province (Sichuan Province) to demonstrate the effectiveness of the proposed models, from which it was found that the overall green urbanization efficiency in Sichuan province was 81.54%, due to an input distribution imbalance and low technical efficiency.